2006
DOI: 10.1111/j.1463-5224.2006.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Canine conjunctival hemangioma and hemangiosarcoma: a retrospective evaluation of 108 cases (1989–2004)

Abstract: Canine conjunctival tumors of vascular endothelial origin are common, although under-reported. The purpose of this study was to evaluate the epidemiology of and potential risk factors for these tumors. This study evaluated 108 cases (70 hemangiomas, 38 hemangiosarcomas) from 8300 canine submissions between 1989 and 2004. Signalment, location, pigmentation, size, duration, diagnosis, margins, ancillary therapy, and geographic location were recorded. Follow-up information was available for 49 cases. Each case wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
101
1
30

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(137 citation statements)
references
References 42 publications
5
101
1
30
Order By: Relevance
“…However, animals with pale skin and hair color are at increased risk of solar injury 1. The 2 most prevalent neoplastic lesions induced by ultraviolet irradiation are cutaneous squamous cell carcinoma (SCC) in dogs and cats, and cutaneous hemangiosarcoma 1, 2, 3, 4, 5, 6, 7…”
mentioning
confidence: 99%
“…However, animals with pale skin and hair color are at increased risk of solar injury 1. The 2 most prevalent neoplastic lesions induced by ultraviolet irradiation are cutaneous squamous cell carcinoma (SCC) in dogs and cats, and cutaneous hemangiosarcoma 1, 2, 3, 4, 5, 6, 7…”
mentioning
confidence: 99%
“…In dogs, primary involvement occurred within nonpigmented epithelium along the leading edge of the nictitating membrane and temporal bulbar conjunctiva ( Figure 1D, E) (PIRIE et al, 2006). PIRIE et al (2006), found that the numbers of confirmed cases Ciência Rural, v.40, n.10, out, 2010.…”
Section: Conjunctiva E Nictitating Membrane Hemangioma and Hemangiosamentioning
confidence: 99%
“…Despite their high incidence, a definitive diagnosis is not always performed (PIRIE et al, 2006). In a large case series that examined 70 hemangiomas and 38 hemangiosarcomas of dogs, and 6 hemangiomas and 2 hemangiosarcomas of cats, revealed that average age upon presentation was 8.6 years in dogs, and 10.6 years in cats; there was no sex or breed predisposition for dogs, whereas domestic short hair cats where overrepresented (PIRIE et al, 2006).…”
Section: Conjunctiva E Nictitating Membrane Hemangioma and Hemangiosamentioning
confidence: 99%
See 2 more Smart Citations